Data Privacy and Confidentiality in Data Breach on Cloud Computing - Shahzad, Faisal; Din, Roshidi; Ghazali, Osman (International Journal of Engineering and Technology, 2018)
The preservation of data security in cloud environment has been identified as one of the key challenges in the field of cloud computing. The breach of data privacy and confidentiality has decreased the shift of enterprises to the cloud environment. However, there is currently no single definition of the concepts of data privacy and data confidentiality that could be generalized. Existing definitions of data privacy and confidentiality are complex, ambiguous and interchangeably used. This lack of clarity leads to confusion and potentially to ineffective and inefficient efforts to secure privacy and confidentiality of data from breach. The aim of this study is threefold. Firstly, this paper tends to explores the existing definitions of data privacy and data confidentiality in cloud computing. Secondly, it purports to examine the association of data breach with data privacy and confidentiality. Lastly,it proposes new operational definitions in order to differentiate between the concepts of data privacy and data confidentiality and data breach. The studies suggested that the concept of data privacy and data confidentiality in cloud computing is closely related and both are prone to breach within cloud security domain. Therefore, devising strategies and techniques to secure privacy and confidentiality of data can ultimately results in reduction of data breach.Â Â